Enhancing Students’ Knowledge of Clean and Healthy Living Practices at MTs Darul Ulum Sasa, Ternate City - Mutmainnah Mutmainnah; Muhammad Subhan A. Sibadu; Rufaidah Azzahrah; Nurul Izzah H. L. Pasi (Shihatuna : Jurnal Pengabdian Kesehatan Masyarakat, 2026)
Clean and Healthy Living Behavior (PHBS) is a promotive and preventive effort that plays a crucial role in preventing environment-based diseases, particularly among school-aged children in coastal areas. MTs Darul Ulum Sasa, located in the coastal area of Ternate City, is a school where the implementation of PHBS remains relatively low. This community service activity aimed to improve students' knowledge regarding PHBS through health education. A participatory approach was employed, consisting of pre-test, interactive educational sessions, discussions, and post-test. The activity was conducted on April 11, 2025, involving 18 students of MTs Darul Ulum Sasa. A multiple-choice questionnaire was used as the evaluation instrument to measure students' knowledge before and after the educational intervention. Data were analyzed using the Wilcoxon test. The results showed a significant increase in the mean knowledge score from 59.09 ± 29.10 in the pre-test to 79.55 ± 15.27 in the post-test, with a statistically significant difference (p < 0.05). These findings indicate that PHBS education was effective in enhancing students' understanding of the importance of personal and environmental hygiene.